Improving martial arts education through gamified learning: The case of Pencak Silat with Quizizz - Ariadi, M. Gusti; Bayu, Wahyu Indra; Solahuddin, Soleh (CV Rezki Media, 2025)
Background: The use of digital media in learning is an innovative effort to improve the quality of the teaching and learning process, including in physical education, particularly in the subject of Pencak Silat Objectives: This study aims to determine the effect of using the Quizizz application on the learning outcomes of Pencak Silat among students at Public Senior High School 1 Indralaya Selatan. Methods: This research was conducted using a quantitative approach. The design used is a one-group pretest-posttest design. In this design, students are given a pretest before treatment, followed by a learning treatment using Quizizz media. After the treatment is completed, a posttest is administered. The population in this study consists of all 11th-grade students at Senior High School 1 Indralaya Selatan, totaling 149 students. From that population, a simple random sample of 30 students will be taken to serve as the research sample. The research instruments include a cognitive test in the form of multiple-choice questions and a psychomotor test in the form of basic pencak silat technique practice. Then the data were analyzed using the Shapiro-Wilk normality test to ensure data distribution, followed by a paired sample t-test using IBM SPSS Statistics version 30.0.0.0 (172) software. Results: The analysis shows a significant increase in pretest to posttest scores, both in cognitive aspects (from an average of 37.87 to 58.83) and psychomotor aspects (from an average of 5.43 to 8.70). In the paired sample t-test, the significance value showed <0.001, indicating a significant effect of Quizizz media on students' learning outcomes. Conclusions: This research concludes that the Quizizz application effectively enhances the understanding of concepts and fundamental movement skills of pencak silat in a fun and interactive way.